2016
DOI: 10.1002/art.39667
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Versus Adalimumab in the Treatment of Refractory Inflammatory Uveitis: A Multicenter Study From the French Uveitis Network

Abstract: Objective. To analyze the factors associated with response to anti-tumor necrosis factor (anti-TNF) treatment and compare the efficacy and safety of infliximab (IFX) and adalimumab (ADA) in patients with refractory noninfectious uveitis.Methods. This was a multicenter observational study of 160 patients (39% men and 61% women; median age 31 years [interquartile range 21-42]) with uveitis that had been refractory to other therapies, who were treated with anti-TNF (IFX 5 mg/kg at weeks 0, 2, 6, and then every 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 36 publications
3
94
1
6
Order By: Relevance
“…The participants had an overall response rate of 93% at 12 months. 23 Most recently, the main study data from VISUAL I and VISUAL II studies also demonstrated the efficacy and safety of adalimumab (anti-TNFα) to treat uveitis. 13,14 Low adalimumab immunogenicity was observed in both VISUAL I and VISUAL II studies and was in the range of rates observed in other disease states.…”
Section: Discussionmentioning
confidence: 99%
“…The participants had an overall response rate of 93% at 12 months. 23 Most recently, the main study data from VISUAL I and VISUAL II studies also demonstrated the efficacy and safety of adalimumab (anti-TNFα) to treat uveitis. 13,14 Low adalimumab immunogenicity was observed in both VISUAL I and VISUAL II studies and was in the range of rates observed in other disease states.…”
Section: Discussionmentioning
confidence: 99%
“…; Vallet et al. ; Durrani et al ) and the capability to rapidly reach therapeutic drug levels in the eye when used intravitreally (Modorati & Miserocchi ). One reason that may explain the lack of efficacy or long‐term efficacy in some of the studies is that their mechanisms of action may not be effective when administered locally in the eye, given the systemic nature of the diseases underlying the inflammatory process (Suhler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although not formally approved for NIU, there are an important number of studies with infliximab specifically in two underlying conditions: Behc ßet disease and juvenile idiopathic arthritis (Levy-Clarke et al 2014;Cordero-Coma & Sobrin 2015). Moreover, evidence of the efficacy and safety of adalimumab and infliximab in adult NIU may also be found in case reports (Leccese et al 2011;Takase et al 2011;Zmuda et al 2013;Capote et al 2014;Ermetcan et al 2014;Achille et al 2016;Sakurai et al 2016), retrospective case series (Mushtaq et al 2007;Sobrin et al 2007;Handa et al 2011;Okada et al 2012;Al Rashidi et al 2013;Dobner et al 2013;Alfawaz et al 2014;van Denderen et al 2014;Interlandi et al 2014;Kruh et al 2014;Takeuchi et al 2014;Kim et al 2016;Vallet et al 2016;Durrani et al 2017) and prospective case series (Joseph et al 2003;Diaz-Llopis et al 2008;Rudwaleit et al 2009;Suhler et al 2009Suhler et al , 2013D ıaz-Llopis et al 2012;Erckens et al 2012).…”
Section: Rationale For Intravitreal Administration Of Anti-tnf Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…A 2016 study found 28% of patients experienced side effects with 13% deemed ‘serious’, such as hypersensitivity reactions ( n  = 10), autoimmune disease ( n  = 6) and neoplasia ( n  = 4) [64]. These adverse effects are most likely due to the murine origin of the variable region of the molecule, and can be attenuated by concomitant anti-histamine and pain-relief medication.…”
Section: Introductionmentioning
confidence: 99%